Analysis of the use of video media on the learning interest of BI Class Students in Elementary School Teacher Education at the Universitas Terbuka - Anggraini, Cicilia Clara Devi (Universitas Trunojoyo Madura, 2022)
This study aims to analyze the use of video media on the learning interest of elementary school teacher education students. The population used in this study were all students of the BI Service Center class at the Universitas Terbuka Purwodadi-Grobogan Campus 1 Pancasila Vocational School for the 2022.2 academic year. Meanwhile, the sample in this study were some students of the BI Service Center class at the Universitas Terbuka Purwodadi-Grobogan Campus 1 Pancasila Vocational School for the 2022.2 academic year. Data collection techniques used were interviews, observation, documentation, and literature study. The data analysis techniques used in this study are data reduction, data presentation, and drawing conclusions. The results of the analysis show that there is a significant increase in student learning interest when learning activities use video media. This research can be used as input material in developing innovative learning media according to student characteristics.